Port-wine stain/Cutis marmorata telangiectatica congenita. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
In the first days the differential diagnosis between port-wine stain (PWS) and cutis marmorata telangiectatica congenita (CMTC) may be difficult. The differential diagnosis is important because the prognosis of PWS is severer due to the higher frequency of associated malformations and its possible progressive worsening, in contrast with CMTC which tends to improve with time.